Pengembangan Dan Implementasi Website Tourism Mempawah Mangrove Park Kabupaten Mempawah - Ilhamsyah, Ilhamsyah (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – Mempawah Mangrove Park is a mangrove forest area empowered as an ecosystem that always attracts tourists. The problem of partners is that this eco-universe does not yet have a website as a platform to provide information and introduce this tourist attraction digitally. Design/methodology/approach – The method of the activity is conducted in the form of initial observation through interviews and surveys at the activity location, followed by the formulation of activities. The implementation of the PKM includes socialization, training, website installation, and activity evaluation. Findings – Dedication activities to the community with the theme Development and Implementation of Website Tourism Mangrove parks have resulted in a significant improvement in the marketing efficiency of this tourist site.The evaluation was conducted to staff and prospective visitors of Mangrove Park in the form of a questionnaire to measure the success of implementation. On the activities there is marketing efficiency through the development of website, as well as the correct implementation strategy.  Originality/value – Initially, the promotion success rate was only around 46.67%, but after creating a Mangrove Park profile website, the promotion success rate increased to 84.89%.